Buffeting response of a composite cable-stayed bridge in a trumpet-shaped mountain pass. Issue 3 (February 2020) - Shen, Zheng-feng; Li, Jia-wu; Gao, Guang-zhong; Xue, Xiao-feng
Previous research showed that wind characteristics were influenced by terrain. To accurately calculate the wind-induced bridge response, this article presented a comprehensive investigation of the wind characteristics of a trumpet-shaped mountain pass by long-term monitoring. Basic strong wind characteristics such as the wind rose, turbulence intensities, turbulence length scales, turbulence spectra and normalized cross-spectrum were discussed using 10 min intervals. Due to the different types of terrain on the two sides of the bridge site, this article attempted to reflect the influence of the terrain on the wind characteristics in different wind directions. The scatter plots of wind characteristics were presented directly on the terrain map. The effects of the turbulence characteristics, mean wind speed and aerodynamic admittance function on buffeting response of the composite cable-stayed bridge were discussed by the multimode coupled frequency domain. The results show that the wind profile is extremely twisted. The larger turbulent integral scale and the lower turbulence intensity appear in the direction along the river. The effect of the mean wind speed on the buffeting response is greater than that of the fluctuating wind characteristics. The aerodynamic admittance function proposed by Holmes has the largest reduction in buffeting response.